UPAYA MEMBANGUN PARADIGMA QURANI DALAM MENGATASI KENAKALAN REMAJA DAN PENYALAHGUNAAN NARKOBA - Zachratu Tsania Dzelhyjja; Dhea Ramadhani; Alphani Amelia; Cayank Aulia; Aisyah Aini; Suci Ramadhani; Hana Nouftalifa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Juvenile delinquency and drug abuse are social problems that negatively affect the development of young generations. These issues are influenced by various factors, including spiritual crises, weak family resilience, peer pressure, and unfavorable social environments. From an Islamic perspective, the Qur'an serves as a guide for life that can shape adolescents' character and behavior. This study aims to analyze the concept of the Qur'anic paradigm in adolescent life, identify the factors contributing to juvenile delinquency and drug abuse, and formulate strategies to address these problems based on Qur'anic values. The study employed a qualitative approach using a library research method. Data were collected from the Qur'an, Hadith, books, scientific journal articles, and relevant previous studies. Data analysis was conducted through content analysis, including data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that the Qur'anic paradigm functions as a framework for developing spiritual awareness, self-control, and positive character among adolescents. The main causes of juvenile delinquency and drug abuse include existential and spiritual crises, family dysfunction, and peer influence. Preventive efforts can be implemented through strengthening faith, optimizing worship as spiritual therapy, and establishing a supportive social environment (biah shalihah). The Qur'anic paradigm offers preventive, curative, and rehabilitative approaches for developing morally upright and drug-free young generations.